Factor that influences online impulse purchase among generation Y in Malaysia - Chan, Man Ting; Chong, Chia Man; Heng, Zheng Yuan; Goh, Jing Heng; Yin, Weng Hong (2019)
The aim to carry out this research is to investigate the determinants that influence Online Impulse Purchase (OIP) among Generation Y (Gen Y) in Malaysia. Digital purchasing convenience has brought a significant impact on OIP among consumers. Different behaviour had cause consumers to involve themselves in these circumstances. Traits (T), Social Influence (SI), Purchase Intention (PI) and Diderot Effect (DE) were the four Independent Variables (IV) which affected by the mediator consist of Positive Affect (PA) and Negative Affect (NA). Based on a conceptual framework, CET was adapted and used in our research. 340 sets of questionnaire were collected from the respondents. The data gathered from respondents is analysed by Partial Least Squares Structural Equation Modelling (PLS-SEM). This study provides managerial implications to the firms, consumers, and government. Consumers and government can use the research outcome to find out the way to reduce OIP. Firms can use the research outcome to gain more sales.